Outcome measures in muscular dystrophy rehabilitation: an ICF content comparison approach to the most commonly used MD scales - Mihaela Taranu; Raquel Sebio-García; José C. Milisenda; Aida Alejaldre; Xavier Pastor; Sarah Laxe (Journal of Rehabilitation Medicine)
Introduction: Functioning is the reason to be of rehabilitation as it is essential to the lives of people who suffer from a disease. The International Classification of Functioning, Disability and Health (ICF) can help in designing a functioning profile of a patient, identifying needs for rehabilitation plans and measuring the results of an intervention.